FAKTOR-FAKTOR TERKAIT KEPATUHAN KEPERAWATAN DALAM PELAKSANAAN STANDAR PELAYANAN RSU AL-AZIS - Raja Khairul; Gerry Silaban; Fithri Handayani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
Universal / Standard Precautions are recommended to prevent exposure to blood-borne infectious diseases such as HIV, Hepatitis B Virus, and Hepatitis Virus in health services, in Elpi Al-Azis General Hospital Rantauprapat, the compliance with Universal / Standard Precautions among nurses is low, it can be seen from accident cases syringes that occurred among nurses in 2007-2019 were 6, 4, and 8 cases respectively. This study was an Analytical Survey using a cross sectional design with 60 respondents as a population and 52 nurses as sample.From the results of the chi square test, the variables significantly associated with nurse compliance with the application of universal / standard precautions are knowledge p value = 0.003,perception of risk p value = 0.001,Barriers to risk p value = 0.008, Perception regarding policy p value = 0.004, workload p value = 0.001, training and availability of Private Protective Equipment p Value 0.010. By analyzing with multivariate show that there is the most dominant variable is workload p value = 0.042, Exp (B) = 4.973 with CI 95% (0.835- 23.253). From the results of the study it can be concluded that there is a significant relationship between perceptual factors and workload factors regarding policy with nurse compliance in the implementation of universal / standard precautions in Elpi Al-Azis Hospital Rantauprapat in 2019. It is expected that there is a policy from Hospital management in implementing workload so that nurses' perceptions have a positive impact on carrying out tasks systematically.